The parental home as labor market insurance for young Greeks during the crisis - Rebekka Christopoulou; Maria Pantalidou (Global Labor Organization (GLO), 2017)
Labor market conditions in Greece have severely deteriorated during the crisis, affecting youths the most. Using the Greek crisis as a case-study, this paper examines the role of the family as a social safety net for its young members. Specifically, we test the relationship between youth labor outcomes and parental co-residence, whether this relationship has become stronger during the crisis, and the degree to which the relationship is causal. Our results confirm that the parental home is a refuge both for jobless youth and for those in poorly paid, insecure jobs, and this role has intensified during the crisis. We find no reverse causality between co-residence and employment status for young men, and significant reverse causality for women. This finding implies that all youths live in the parental home when they are in need themselves, but it is young women not men who live with parents when parents are in need or for cultural reasons.
Keywords: J12; J21; 330; Living arrangements; parental coresidence; youth employment; great recession; Greece